2001
DOI: 10.1515/cclm.2001.120
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine in Cerebrovascular Disease: an Independent Risk Factor for Subcortical Vascular Encephalopathy

Abstract: Hyperhomocysteinemia is a risk factor for obstructive large-vessel disease. Here, we studied plasma concentrations of homocysteine and vitamins in patients suffering from subcortical vascular encephalopathy (SVE), a cerebral small-vessel disease leading to dementia. These results were compared to the homocysteine and vitamin plasma concentrations from patients with cerebral large vessel disease and healthy control subjects.Plasma concentrations of homocysteine, vascular risk factors and vitamin status (B 6 , B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Among the three small-population studies regarding the positive association of hyper-Hcy with lacunar infarction (4-6), two indicated a weak association (4,6), while the other indicated that the association was a little stronger than that with large-artery atherosclerosis (5). In addition, hyper-Hcy has been suggested to associate with subcortical vascular encephalopathy (14,15). Although the pathology of deep perforating arteries and subcortical microvessels may differ, these findings suggest that hyper-Hcy contributes to small artery diseases in a fashion different from atherosclerosis, possibly including the formation of microatheroma.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three small-population studies regarding the positive association of hyper-Hcy with lacunar infarction (4-6), two indicated a weak association (4,6), while the other indicated that the association was a little stronger than that with large-artery atherosclerosis (5). In addition, hyper-Hcy has been suggested to associate with subcortical vascular encephalopathy (14,15). Although the pathology of deep perforating arteries and subcortical microvessels may differ, these findings suggest that hyper-Hcy contributes to small artery diseases in a fashion different from atherosclerosis, possibly including the formation of microatheroma.…”
Section: Discussionmentioning
confidence: 99%
“…Age, hypertension, and hyperhomocysteinemia are known risk factors for both arteriolosclerosis and WML (Bertsch et al, 2001;Breteler et al, 1994;Vermeer et al, 2002) and post mortem pathological associations between WML and arteriolosclerosis have been described (Awad et al, 1986;van Swieten et al, 1991).…”
Section: Etiologymentioning
confidence: 99%
“…[7][8][9] Increasing age and vascular risk factors such as hypertension, diabetes, and hyperhomocysteinemia are related to the degree of WMLs. 10,11 The clinical relevance of WMLs is controversial; however, recent data confirm the coexistence of vascular dementia, gait unsteadiness, and urinary incontinence subsumed in the syndrome of subcortical vascular encephalopathy (SVE) with severe WMLs. 12 There is growing evidence that the progression of WMLs is associated with progressive functional deficits such as gait disturbance 13 and upper limb discoordination, 14 and a large ongoing European trial 15 intends to clarify the issue of increasing disability in the elderly on the basis of progressive WMLs.…”
mentioning
confidence: 99%